Serum Ferritin in Preeclampsia and Eclampsia: A Case Control Study - Fatima, Nusrat; Islam, Ferdousi; Noor, Laila; Das, Shila Rani; Zeba, Dilruba; Zesmin, Fahmida (Faridpur Medical College Journal, 2013)
Preeclampsia is a pregnancy specific, multi-system disorder of unknown etiology characterized by new onset of elevated blood pressure & proteinuria after 20 weeks of gestation. Globally preeclampsia and other hypertensive disorders of pregnancy are a leading cause of maternal and infant illness and death. But the exact pathophysiology is yet to be explored. It was a case control study and was conducted during the period of January 2010 - December 2010 in the department of Obs & Gynae DMCH and dept. of Biochemistry of BSMMU. The main objective of the study was to evaluate the association of serum ferritin and iron in preeclampsia & eclampsia. A total 100 pregnant women were included in this study. Of them 50 preeclamptic or eclamptic, nonanaemic patients not in labour (26-40weeks) were taken as case and 50 normotensive pregnant women were taken as control. Mean Serum ferritin level in case and control group was 100.03 ± 123.52 ?gm/L and 31.53 ± 20.86 ?gm/L respectively which is highly significant (P< 0.001). Out of 50 cases ferritin level was raised in 10 cases (20%). In 80% cases ferritin level was below the cut-off value that is normal or below normal but in 100% of controls had ferritin level below the cut off value. DOI: http://dx.doi.org/10.3329/fmcj.v8i1.16892 Faridpur Med. Coll. J. 2013;8(1): 18-21